Cerebellar related social and motor behavior in Red Junglefowl selected for high or low fear of humans - Gjøen, Johanna; Jensen, Per (Frontiers in Ethology, 2025)
Domestication involves selection for tameness, which can lead to correlated changes in behavior, morphology, and brain physiology. One part of the brain that has become relatively larger in domesticated chickens, as well as in Red Junglefowl (Gallus gallus) selected for increased tameness, is the cerebellum, which is involved with an extensive variety of behaviors. This study explored the impact of selection for high (HF) or low (LF) fear of humans in Red junglefowl (RJF) on cerebellum-linked traits such as motor coordination, balance, and social navigation. Using an obstacle course, a rotarod test, and a social recognition test we assessed the performance of HF and LF birds from the 14th generation of selection lines. While HF birds completed the obstacle course more quickly (p < 0.001), there were no significant differences in locomotory coordination. LF birds exhibited more reorientation pauses, potentially linked to exploratory behavior and reduced fearfulness. In the rotarod test, the latency time did not reach statistical significance (p = 0.1). The social recognition test revealed a clear social preference in the HF line, with preference for a non-aggressive rooster, but no significant preferences in the LF line. Our findings suggest that the selection for tameness, previously associated with increased cerebellar size, influences the approach to transverse an obstacle course in order to regain social contact, and social navigation as measured by choice of social partner. Furthermore, a possible but non-significant link to motor control, as measured by the ability to stay on a rotarod, was observed. This suggests that the tameness-induced changes in cerebellum may affect social behavior such as social navigation, rather than affecting motor control.